Fat-Tails and their (Un)Happy Endings : Correlation Bias and its Implications for Systemic Risk and Prudential Regulation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The correlation bias refers to the fact that claim subordination in the capital structure of the firm influences claim holders' preferred degree of asset correlation in portfolios held by the firm. Using the copula capital structure model, it is shown that the correlation bias shifts shareholder preferences towards highly correlated assets, making financial institutions more prone to fail and increasing systemic risk given interconnectedness in the financial system. The implications for systemic risk and prudential regulation are assessed under the prism of Basel III, and potential solutions involving changes to the prudential framework and corporate governance are suggested.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet